Cardiotocography in a perinatal armamentarium: boon or bane? - Xavier, Ambily Anu; Pandey, Deeksha; Dogra, Luvdeep; Lewis, Leslie Edward (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: As electronic foetal monitoring (EFM) is becoming commoner in obstetric armamentarium, so are caesarean deliveries. Present study was conducted with an aim to find out correlation between cardiotocography (CTG) findings, intraoperative findings, and perinatal outcome in subjects who underwent emergency caesarean deliveries. We also intended to estimate the sensitivity, specificity and positive predictive value of CTG in diagnosing foetal distress. Methods: A total of 271 women were included. Based on the CTG findings, the patients were divided into two groups: A) Case group: comprising subjects with Category II (suspicious) and Category III (pathological) CTG tracings; B) Control group: comprising subjects with Category I CTG tracings. Results: We found that 90.5% women with suspicious and pathological CTG (cases) undergoing emergency caesarean had one or the other abnormal per-operative findings that might cause foetal distress or CTG abnormality. Around a third (33.7%) with abnormal CTG had normal per-operative findings and good neonatal outcome suggesting false positivity. APGAR score of less than 5 at 5 minutes was seen in 17.9% of patients with pathological CTG. The sensitivity, specificity, positive predictive value and negative predictive value of CTG for prediction of an abnormal perinatal outcome were found to be 90.5, 66.3, 44.9, and 95.8 respectively. Conclusions: CTG should only be used as a screening tool for monitoring of foetal status during labour. It is worth remembering that normal CTG is more predictive of normal outcomes than abnormal CTG regarding abnormal outcomes.